2019
DOI: 10.1074/mcp.ra119.001611
|View full text |Cite
|
Sign up to set email alerts
|

Global Lysine Crotonylation and 2-Hydroxyisobutyrylation in Phenotypically Different Toxoplasma gondii Parasites

Abstract: The proteomes of the extracellular stage of the two phenotypically different Toxoplasma gondii strains, RH strain and ME49 strain, were systematically analyzed using an LC-MS/MS approach, and the global lysine crotonylation and 2-hydroxyisobutyrylation of the two parasite strains were deeply investigated. The global maps of lysine crotonylation and 2-hydroxyisobutyrylation of the proteomes of the two parasite strains will provide a valuable resource to facilitate the illumination of the biology of the zoonotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 71 publications
7
46
4
Order By: Relevance
“…Lysine crotonylation and 2hydroxyisobutyrylation occurred on proteins mainly located in the cytosol of both parasites and RBCs, mediating diverse metabolic pathways (Fig. S3A and B), similar to our previous findings in Toxoplasma gondii(23). For the RBC proteins, acylation including acetylation, crotonylation, and 2-hydroxyisobutyrylation mainly occurred in proteins associated with sugar metabolism, such as in glycolysis/gluconeogenesis and pentose phosphate pathways, and oxidative stress, proteasome, de novo protein folding, hypoxia-inducible factor (HIF)-1 signaling pathway, and cadherin binding.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Lysine crotonylation and 2hydroxyisobutyrylation occurred on proteins mainly located in the cytosol of both parasites and RBCs, mediating diverse metabolic pathways (Fig. S3A and B), similar to our previous findings in Toxoplasma gondii(23). For the RBC proteins, acylation including acetylation, crotonylation, and 2-hydroxyisobutyrylation mainly occurred in proteins associated with sugar metabolism, such as in glycolysis/gluconeogenesis and pentose phosphate pathways, and oxidative stress, proteasome, de novo protein folding, hypoxia-inducible factor (HIF)-1 signaling pathway, and cadherin binding.…”
supporting
confidence: 90%
“…were predominant in the early stages (Supplemental Data S12, and to be further analyzed in a later section). This indicated that in the early stage of P. falciparum development, not only phosphorylation and acetylation (28) but also 2hydroxyisobutyrylation may exert similar functions in gene activation, as was also observed in a recent study of T. gondii (23). In addition, the heat shock protein 70 (HSP70) family members were mainly modified by 2-hydroxyisobutyrylation apart from phosphorylation and crotonylation in Cluster 1 (Supplemental Data S12); they are known to be important in protein homoeostasis and protein trafficking across the PV as chaperones and immunogens (29,30).…”
Section: The Overall Ptmomics Of P Falciparum and Infected Erythrocytessupporting
confidence: 76%
“…The yeast histone acetyltransferase complex NuA4 and human acetyltransferase Tip60 have been shown to function as enzymes to catalyze K hib , while histone deacetylase 2 (HDAC2) and histone deacetylase 3 (HDAC3) function as the major enzymes to remove 2hydroxyisobutyryl from K hib in mammalian cells (Huang et al, 2018), suggesting that there may be an internal relation between K ac and K hib . In recent years, K hib has been detected and characterized in both histone and non-histone proteins in several species using newly developed modern techniques in molecular biology and mass spectrometry (Huang et al, 2017;Meng et al, 2017;Yu et al, 2017;Dong et al, 2018;Yin et al, 2019). For example, a total of 6,548 unique K hib sites on 1,725 proteins were identified in human cells (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an evolutionarily conserved short-chain lysine acylation modification dubbed lysine 2-hydroxyisobutylation (K hib ) has been reported, which introduces a steric bulk with a mass shift of +86.03 Da ( Supplementary Figure 1A ) and neutralize the positive charge of lysine ( Dai et al, 2014 ; Xiao et al, 2015 ). It involves various biological functions including biosynthesis of amino acids, starch biosynthesis, carbon metabolism, glycolysis / gluconeogenesis and transcription ( Dai et al, 2014 ; Huang et al, 2017 , 2018a ; Li et al, 2017 ; Meng et al, 2017 ; Yu et al, 2017 ; Wu et al, 2018 ; Yin et al, 2019 ). For instance, the decrease of this modification on K281 of glycolytic enzyme ENO1 reduces its catalytic activity ( Huang et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%